Inclusive Education and ICT: Assistive Technologies for People with Sensory Disabilities (Docentes 2.0 Journal, 2021)
The use of technology within the educational space plays a vital role in developing innovative teaching materials or resources. Despite the significant changes that technology has with it, it is possible to question the fiscal, educational institutions of the Ecuadorian Ministry of Education, where the lack of knowledge regarding the use of digital educational resources in the inclusion of people with sensory disabilities is still evident. Thus, this research originated the integration of ICT information and communication technologies as a didactic resource in the communication and teaching-learning processes generated in the educational community. The research process used the mixed approach, where 35 teachers from different educational institutions participated, who were applied as instruments based on the LIKERT scale survey, an-interview, and direct observation and bibliographic review. A diversity of technological resources that can use in educational inclusion processes was evidenced among the results obtained. We can mention digital pictograms, infographics, and mobile applications, strengthening the communication and teaching-learning process of the academic community. Consequently, it can assert that incorporating technologies in educational communities supports the teaching-learning operations and makes the educational inclusion processes more widespread.
Keywords: Inclusive education; Inclusion; didactic resource; ICT; digital applications